A STUDY ON THE ABILITY ON THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITY OF RIAU IN USING REDUCED ADVERB CLAUSES IN SENTENCES - Octria, Verindha; Delfi, Syofia; Sumbayak, Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This descriptive study aimed to find out the ability of fourth semester students of English Study Program of University of Riau in using reduced adverb clauses in sentences, and to analyze kinds of students’ difficulties in using reduced adverb clauses in sentences. This study was based on the students’ problem where they were still confused in using reduced adverb clauses in sentences even they had learnt it on second and third semesters. They will have any subject in the next semester that related to this topic, in this case that is TOEFL Preparation. Therefore, it was needed to do some research in order to know their abilities in using reduced adverb clauses in sentences. This research was conducted in two sessions; try out and real test. The instruments of this study were 40 questions and it was in transformation/ changing the passage test. The research finding shows that fourth semester students of English Study Program of University of Riau were still less average in using reduced adverb clauses. Their mean score was only 48 in the try out test, then in the real test students’ mean score was 50. This research also proves that the most difficult kind of reduced adverb clauses for students was reduced in passive since their mean score was only 30. Based on this finding, it was suggested to fourth Semester Students of English Study Program of Teachers’ Training and Education Faculty in University of Riau to re read and practice materials about reduced adverb clauses and re recognise and surely practiceabout how to make passive sentence again properly.Keywords: grammar, using reduced adverb clauses, fourth semester students’ ability